The Epidemiology of Primary Biliary Cholangitis in European Countries: A Systematic Review and Meta-Analysis. (21st June 2021) - Gazda, Jakub; Drazilova, Sylvia; Janicko, Martin; Jarcuska, Peter
Abstract : Background . Primary biliary cholangitis (PBC) is a chronic autoimmune cholestatic liver disease with wide ranges of reported incidence and prevalence. Aim . To map the incidence and prevalence of PBC in European countries from 2000 through 2020. Methods . Following PRISMA recommendations, we searched the Medline and Scopus databases for studies with information on either the incidence or prevalence of PBC. After data extraction, we used a random-effects model to estimate both the pooled annual incidence rate and pooled point-prevalence rate and performed subgroup analyses to identify components contributing to between-study heterogeneity. Results . We performed a qualitative and quantitative analysis of 18 studies. The pooled point-prevalence rate was 22.27 cases per 100, 000 inhabitants (95% CI: 17.98–27.01), and the pooled annual incidence rate was 1.87 new cases per 100, 000 inhabitants (95% CI: 1.46–2.34). In the subgroup analyses, we proved that a small part of the between-study heterogeneity is significantly associated with a history of being part of the Eastern Bloc.